2017
DOI: 10.1007/s00221-017-4876-9
|View full text |Cite
|
Sign up to set email alerts
|

Cortical activity predicts good variation in human motor output

Abstract: Human movement patterns have been shown to be particularly variable if many combinations of activity in different muscles all achieve the same task goal (i.e., are goal-equivalent). The nervous system appears to automatically vary its output among goal-equivalent combinations of muscle activity to minimize muscle fatigue or distribute tissue loading, but the neural mechanism of this "good" variation is unknown. Here we use a bimanual finger task, electroencephalography (EEG), and machine learning to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…More recent work in non-human primates, however, supports an organization of cortical activity that is compatible with the synergy framework [257]. When searching for neural correlates of synergies in humans, a recent study revealed that the cortical representation of hand postures can be better accounted for by using a synergy-based network than somatotopic or muscle-based models [258], which is compatible with the view of cortical organization of finger movement being shaped by habitual use [259], and even goal equivalence in finger actions being implemented at a cortical level [260].…”
Section: Prescriptive Vs Descriptive Synergiesmentioning
confidence: 67%
“…More recent work in non-human primates, however, supports an organization of cortical activity that is compatible with the synergy framework [257]. When searching for neural correlates of synergies in humans, a recent study revealed that the cortical representation of hand postures can be better accounted for by using a synergy-based network than somatotopic or muscle-based models [258], which is compatible with the view of cortical organization of finger movement being shaped by habitual use [259], and even goal equivalence in finger actions being implemented at a cortical level [260].…”
Section: Prescriptive Vs Descriptive Synergiesmentioning
confidence: 67%
“…Importantly, motor synergies and visual gain support the possibility that an altered amount of visual feedback may influence hierarchical multi-levels involved in sending neural control signals that potentially modulate elemental variables stabilizing task performances across multiple trials 27 . Two sets of investigators reported higher cortical activation patterns in the premotor cortex when individuals produced increased motor synergies across bimanual force control trials 35 , 36 . Interestingly, higher visual gain conditions improved the accuracy of isometric force control with greater cortical activation in the dorsal premotor region and inferior parietal lobule as compared with lower visual gain condition 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%